Balkan Boundaries and Balkanisation: A Geopolitical Perspective - Türk, Müberra Koçyiğit; Aydın, Murat (İstanbul Üniversitesi, 2025)
The Balkans are a geographical region shaped by the Black Sea, the Sea of Marmara, the Aegean Sea, the Adriatic Sea, and the Danube and Sava rivers. However, there is no single, universally accepted definition of the Balkans. Global and regional actors, geographers, historians, and various authors all perceive the Balkans differently. The concept of "Balkanisation," arising from historical, geographical, ethnic, religious, and geopolitical processes, has introduced another layer of definition to the region. This study examines where the Balkan lands, which are partially separated from Europe, begin and end and why there is no common definition of the Balkans. Concrete spatial and historical analysis methods were employed in this study. This study determined that the Balkans do not entirely coincide with the borders of Southeast Europe. Furthermore, the study demonstrated that definitions of the Balkans are based on geographical features and location, historical, ethnic, religious, sociocultural, and developmental factors. The concept of Balkanisation, emerging from the geopolitical interests of various actors in the region, expresses the reality of fragmentation.
Keywords: Political Geography; Siyasi Coğrafya